Application of Robson’s classification in clinical practice: a tool for quality improvement in obstetrics - S. K., Nafeesa Farheen; K., Shravya Monica; Chhikara , Priya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: The global rise in caesarean section (CS) rates has raised concerns regarding the overuse of the procedure in low-risk pregnancies, leading to potential maternal and neonatal risks. Robson’s classification offers a standardized method to assess CS rates and identify the groups contributing most to these high rates, facilitating targeted quality improvement interventions. Methods: A retrospective observational study was conducted at Vydehi Institute of Medical Sciences, Bengaluru, from June 2024 to December 2024, including 265 deliveries. Data were collected from the hospital’s obstetric registry, and studies under Robson’s classification. Results: The overall CS rate was 54.7%, with 145 out of 265 deliveries being caesarean sections. The highest CS rates were observed in two groups, group 5 (multiparous women with a previous CS, 80%) and group 8 (all multiple pregnancies, including previous CS, 80%). Group 6 showed a 66.7% CS rate (nulliparous breech presentations). Groups 2 and 4 (induced labour) also exhibited elevated CS rates, with 62.5% and 50.0%, respectively. Lower CS rates were noted in multiparous women with spontaneous labour (group 3), which had a rate of 30%. The data revealed that induction of labour and previous caesarean sections were significant contributors to higher CS rates. Conclusions: The study highlights the specific high-risk groups to the overall CS rate. The findings emphasize the need for targeted interventions to reduce unnecessary CS while maintaining maternal and neonatal safety. Future efforts should focus on promoting vaginal birth after caesarean (VBAC).